Problematika Perkawinan Beda Agama Menurut Uu No.1 Tahun 1974 - Maria Anna Liwa; Aji Titin Roswitha Nursanthy; Muhammad Japri (LPPM STIH Awang Long, 2018)
Law No. 1 of 1974 concerning Marriage in Article 2 paragraph (1): Marriage is legal if it is carried out according to the law of each religion and belief. Means the Marriage Law No. 1 of 1974 has not yet confirmed the regulation of interfaith marriages. The tendency to close, make it difficult, or obscure the implementation of community aspirations for interfaith marriage is considered by some to be contrary to the Marriage Law No. 1 of 1974. In Article 6 paragraph (1) of the Marriage Law no. 1 of 1974 states